Sensory Evaluation of Effervescent Nutritional Supplements: Identification and Characterisation of Off-Tastes - Thomas Delompré; Christophe Martin; Loïc Briand; Christian Salles (Molecules)
Nutritional supplements are often characterised by unpleasant tastes or aftertastes, primarily due to the presence of vitamins, minerals, and amino acids as active compounds. These taste defects can be masked by sweeteners or specific flavourings. However, the development of such strategies requires a thorough understanding of the sensory characteristics of nutritional supplements. In the present study, the sensory properties of four effervescent nutritional supplements, differing in composition, were evaluated using Quantitative Descriptive Analysis (QDA) across three modalities: orthonasal and retronasal odour perception, as well as aftertaste and aroma persistence. Bitterness, astringency, and metallic sensations were found to be responsible for the negative sensory attributes of the products in solution. The addition of flavouring agents was found to have either a positive or negative effect on the taste characteristics of the supplements. Indeed, certain fruity notes enhanced sweet and sour sensations and were found to mask negative sensory perceptions, although this effect varied depending both on the nature of the nutritional supplement and on the QDA modalities, mainly due to the oral process progressing. A better understanding of these perceptual interactions could provide a solution for masking strategies, potentially reducing the use of additives that can be expensive and detrimental to health.